Book review Christian von Hirschhausen, Torsten Beckers and Kay Mitusch (eds.) Trends in Infrastructure Regulation and Financing. International Experience and Case Studies from Germany. Cheltenham, Edward Elgar - Voorde, Eddy van de (European Journal of Transport and Infrastructure Research, 2006)
Quite a number of international publishers are aware of the fact that international conferences can be linked to excellent books. So does Edward Elgar Publishing Limited. The publisher presented this book, the result of the international conference on applied infrastructure research held at the Berlin University of Technology in October 2002. It provides an overview of international trends in infrastructure regulation and financing. It also discusses the role of the state and the private sector in infrastructure provision. The editors state that infrastructure provision is increasingly considered to be a key to structural change and economic growth of both developed and emerging economies. At the same time, however, there is still a lot of discussion on the appropriate theoretical framework and policy recommendations to achieve objectives such as efficiency, fairness, and sustainable development.